PERSEPSI MAHASISWA TERHADAP PROSPEK KERJA LULUSAN PROGRAM STUDI PENDIDIKAN GEOGRAFI STKIP PESISIR SELATAN - Veni; Arif, Muhammad; Nazmai Ekaputri, Yanti; Syafti, Okviani; Julis, M. (Riau Education Journal, 2021)
This reseach aims to see students' perceptions in choosing the Geography Education Study Program and how they think about job prospects / job opportunities for the Geography Education Study Program, which some people have unexpected job prospects. Opinions like these make the Geography Education Study Program less attractive. This study uses a descriptive qualitative method. The data collected by observation, interviews and documentation. The informants in this research were students of the 2016-2019 class of Geography Education Study Program. The results of this study indicate that the job prospects of Geography Education graduates are quite good, they do not have to be teachers. According to them, job opportunities for Geography Education graduates can work at BMKG, BPDP, mapping and others, of course, accompanied by the ability / expertise in the field of work that will be carried out later.